2006
DOI: 10.1002/ijc.22184
|View full text |Cite
|
Sign up to set email alerts
|

Recreational physical activity and risk of prostate cancer: A prospective population‐based study in Norway (the HUNT study)

Abstract: Physical activity has been studied in relation to prostate cancer risk, but the findings have been inconclusive. We prospectively examined the association between self-reported recreational physical activity and overall risk of prostate cancer, risk of advanced disease and risk of prostate cancer death in a cohort of 29,110 Norwegian men. Incident prostate cancers were obtained from the Norwegian Cancer Registry, and prostate cancer deaths were obtained from the national Cause of Death Registry. During 17 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 34 publications
3
62
0
2
Order By: Relevance
“…That physical activity is more strongly, inversely related to risk of advanced, high-grade or aggressive prostate cancer has, however, been indicated previously. 8,10,36 Our study supports this with regard to occupational activity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…That physical activity is more strongly, inversely related to risk of advanced, high-grade or aggressive prostate cancer has, however, been indicated previously. 8,10,36 Our study supports this with regard to occupational activity.…”
Section: Discussionsupporting
confidence: 86%
“…Some studies have indicated that an apparent dose-response relationship could be caused by a threshold effect attributable to a higher risk among men who were completely or relatively inactive compared to rest of the population, 4,7,10,36 and to address this issue we evaluated the effect of participation in each of the 4 activities (active versus non-active in each activity) as well as the effect of participation in at least one of the 4 leisure time activities. Furthermore, a linear effect of the number of activities in which the participants were active was investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Further studies are needed to determine whether the exerciseinduced decrease in tissue fat plays a role in the exerciseinduced inhibition of Panc-1 and PC-3 tumor growth. In epidemiological studies, exercise was reported to be associated with a decreased risk of advanced prostate cancer (12,13,25). Additional studies are needed to determine whether exercise decreases the risk or growth of pancreatic cancer in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies on the relationship between physical activity and prostate cancer risk have been inconclusive (8)(9)(10)(11), but large population-based studies suggest that physical exercise is associated with a reduced risk of advanced prostate cancer and prostate cancer death (12,13). In additional studies, the serum from men who exercise inhibited the growth and increased apoptosis in prostate cancer LNCaP cells (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…20,23 Nilsen and associates found an inverse relationship with a Norwegian cohort, and also reported that there was a significant decrease in advanced prostate cancer occurrence with higher levels of physical activity. 37 Although there are a few studies indicating an inverse relationship (ie, lower cancer risk associated with higher levels of activity), several recent studies found no association between physical activity and the prevention of prostate cancer. [38][39][40] According to Friedenreich and Orenstein, the physical activity relationship with prostate and endometrial cancers was only considered probable or possible.…”
mentioning
confidence: 99%